In vitro branched chain amino acid oxidation by porcine mammary tissue - Richert, B.T.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mammary secretory tissue from six (three each of parity 1 and 2) lactating sows (d 10 to 17 of lactation) was obtained via biopsy for in vitro incubation to determine CO2 production fr01TI individual branched chain amino acids. Carbon dioxide production levels as percentages of the 14C-labeled amino acid metabolized by the mammary tissue were 2.57, 1.86, and 4.07% for isoleucine, leucine, and valine, respectively (P< .03). These results indicate that, in the lactating sow mammary gland, valine has the greatest oxidation rate of the branched chain amino acids.
Keywords: Swine; Mammary gland; Sows; Isoleucine; Leucine; Valine